Applying Multilevel Modeling to the Development of Geographic Information Systems - Alvarado, Suilen H.; Cortinas, Alejandro; Luaces, Miguel R.; Pedreira, Oscar; Places, Angeles S. (2019 ACM/IEEE 22nd International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2019)
Multilevel modeling is an approach to model-driven engineering (MDE) in which the number of metamodel levels is not fixed. In this paper, we present and discuss the application of multilevel software modeling to the development of geographic information systems (GIS), and its potential benefits. Different GIS applications may provide different features and functions, but they all share a set of common concepts (regarding spatial data types, operations, services, etc.), common architecture, and a common set of technologies. Although we do not present a complete set of models, we present representative parts of that set (spatial networks, territory decomposition, and trajectories) that, when compared with previous work on MDE applied to GIS, support our proposal that multilevel modeling can provide more benefits to GIS development than just applying a more traditional two-level MDE approach.